Assessment of Heavy Metal Contamination Levels in Market Gardening Soils Used to Grow Onions (Allium Cepa) in the City of Abéché (Eastern Chad) - Abdou, Hamadou; Léopold, Ekengele Nga; Malloum, Mahamat Seid Ali; Bitom, Dieudonné (International Journal of Applied Sciences and Biotechnology, 2023)
The main objective of this study was to assess the level of metal contamination of the soils used in the cultivation of onions in the city of Abéché. Thus, 04 plots were carried out and monitored for a period of five years (05 years). Two traditional plots were chosen in the Arkou site; and two control plots were carried out in the Bagarine site. Soil samples were taken annually (2016 to 2020) after harvesting on a thickness of 0 and 20 cm. In each plot, thirteen (13) samples were taken. After quartering, one (01) representative sample from each plot was retained. The samples were analyzed by optical emission spectrometry at the Food Quality Control Center Laboratory (FQCCL) in Ndjamena. The determination of heavy metal concentrations revealed relatively low levels for Ni, Zn, Cu, Cr and Fe. These levels are generally lower than the reference values ​​for all the plots. Geoaccumulation indices (Igeo) and Contamination factor (Cf) revealed pollution indices. Pb and Cd show contaminations in traditional plots. The correlations (P < 0.05) observed in our study area are positive and significant. This study shows that the use of chemical inputs are sources of soil contamination by heavy metals. Int. J. Appl. Sci. Biotechnol. Vol 11(1): 42-53.